The Effect of Aquatic Exercises on Special Endurance (Strength and Speed) and Achievement Run (800m) for Youth - Ahmed Elewy Arhem; MazinEnhier Lami (Institute of Medico-legal Publications Pvt Ltd, 2022)
The research aims to use Aquatic exercises to develop special endurance and run (800m) for youth toidentify the level of (speed endurance and force endurance) of the participants of the sample membersof the experimental group. The researchers used the experimental method for its suitability to the natureof the study, and the sample was from Wasit Governorate clubs racers. The participants were (12) racers.We were divided into two control and experimental groups. The duration of the experiment was (8)weeks from (28/10/2020 to 10/3/2021). The place of the experiment is in the Al-Gharraf River (a branchof the Tigris River) and the Kut Olympic Stadium. The researchers used tests to speed endurance of adistance (600m), a test to endurance the strength of running by jumping for one minute (Bousing), andan achievement test (800m). The researchers concluded that training in the aquatic medium exercisesaffected the development of special endurance (speed endurance and force endurance) and it had apositive effect in completing the 800m race for youth.